PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIME TOKEN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN REAKSI REDUKSI OKSIDASI DI KELAS X SMA NEGERI 2 SIAK HULU - Henny Devita; R. Usman Rery; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Research on the application of cooperative learning model Time Token has been conducted to improve student learning achievement on the topic stoichiometry at class X SMAN 2 Siak Hulu. This research is experimental research with randomized control group pretest-posttest design. The sample took in the month February – maret 2013. The sample consisted of two class, X3 class as control class. Experimental class is the with cooperative learning model Time Token and Control Class is the class with cooperative learning model Time Token. Analyze of data by used t-test formula. Result of data processing obtained t count>t table is 2,07 > 1,67. It means that the application of cooperative learning model Time Token can improve student achievement on the topic redoks at class X SMAN 2 Siak Hulu with the increasing percentage of 6,299%.Keywords : Cooperative learning, time token, learning achievement, redoks